AN EXPLORATION OF THE ATTRIBUTES OF INTERNATIONAL HARMONISATION INDICES USING THE T-INDEX - W. Astami, Emita; Tower, Greg; Rusmin,; Taplin, Ross (The journal of contemporary issues in business and government, 2006)
This study analyses the degree of harmony of four key accounting policy choices - depreciation policies, type of goodwill treatment, fixed asset valuation and inventory measurement - in 442 companies in five Asia-Pacific countries. The T-Index finds goodwill harmony percentages were only nine percent if non-disclosing companies were considered to be not comparable, 25 percent if excluded and 71 percent if considered comparable to all. Similarly, different assumptions about partial comparability of accounting policy choices resulted in varying scores from 36-61 percent for inventory. The analysis shows that in the Asia-Pacific region there remains a large level of different accounting policies chosen by countries. Concerns about comparability of data for financial statement users thus remain. Closer scrutiny of implicit assumptions contained within harmony indices and consideration of more detailed analysis are also advocated by this study.